Μailing 'Cypriotness': the sensualization of official culture through stamps - Andreou, Sonia; Zantides, Evripides (My University, 2016)
The current study proposes a closer look on the ways in which an object representing the official culture of a state, such as a postage stamp, can be studied as a carrier of ideologies within the spectre of visual communication. Despite the fact that the stamp seems to be an overlooked medium of research in comparison to a country’s touristic branding, or numismatics, it should be read as an important visual text, carrying socio-political implications. Stamps are providers of a national sense of identity and belonging as they are simultaneously government documents and representatives of the country, regarding external and internal audiences. In this way these everyday objects contribute to the shaping of collective identity, through the repetition of their imagery in daily mentality, as Edensor suggests (2002). The current study explores the connoted messages that such an item transfers from the state to its citizens and how this stamp design program is perceived by the citizens of the state. We are furthermore interested in interpreting socio-politically our findings taking into consideration the framework of Cyprus. The research was based on quantitative content analysis data, as well as data gathered through a survey research. Moreover we have chosen to semiotically analyze specific stamp imagery, where the senses are being connoted, through visual representations that are mainly iconic. By combining qualitative and quantitative methods of research we aim to broaden the ways in which postage stamps are studied, proving that visual communication through cultural artefacts like stamps indeed brims with significant information.
Keywords: Postage stamps; Visual communication; Connoted messages; Cyprus